Building a Creative Startup Ecosystem: Case Study of the City of Jakarta in Indonesia - Amin Zaki; Faisal Razak; Nurul Huda (Yayasan Adra Karima Hubbi, 2024)
The growth of creative startups has become a key driver of economic development in many cities around the world, including Jakarta, Indonesia. However, despite its potential, Jakarta faces challenges in establishing a robust ecosystem that supports creative startup growth. Understanding how to build an effective ecosystem for creative startups in Jakarta is crucial for fostering innovation, job creation, and economic diversification. This study aims to analyze the key components and challenges involved in building a creative startup ecosystem in Jakarta, focusing on the role of government, private sector, and academic institutions in nurturing this ecosystem. A qualitative case study approach was employed, utilizing interviews with key stakeholders, including entrepreneurs, government officials, investors, and academics. Data was also collected through a review of existing reports, articles, and policy documents related to Jakarta's startup ecosystem. The research reveals that Jakarta's creative startup ecosystem is still in its early stages but is showing promise. Key challenges identified include limited access to funding, lack of mentorship, and regulatory hurdles. However, initiatives such as government support programs, collaborative spaces, and growing investment interest have provided significant momentum. Building a successful creative startup ecosystem in Jakarta requires concerted efforts from various stakeholders. A collaborative approach between the government, private sector, and academic institutions is essential for overcoming existing barriers and fostering a more sustainable and inclusive startup environment.